Pengaruh Massa Perekat Tapioka Terhadap Durabilitas Biobriket dari Arang Kulit Singkong - Fitriyano, Gema; Sari, Fatma; Susanty, Susanty; Ar Rahim, Dicka; Nabilah, Rifa; Wulandari, Qodirani Apri (Universitas Trunojoyo Madura, 2024)
Commercially competitive in the global market, bio-briquettes derived from coconut shell charcoal have been extensively manufactured and meet all standard prerequisites. Bio-briquettes sourced from different biomass materials, with calorific values that meet the criteria, have not entered commercial production. Currently, they remain in the research and development phase. One of the reasons is the suboptimal durability value of the bio-briquettes, causing the products to easily break during distribution and usage. This research aims to determine the optimal amount of binder in the production of bio-briquettes from cassava peels. This is because cassava peels have calorific values that meet the requirements and have a huge potential for commercial-scale production. This study utilizes cassava peel charcoal as the raw material mixed with tapioca binder in variations of 9%, 10%, 11%, 12%, and 13% of the cassava peel charcoal mass. The optimal percentage of tapioca binder mass was found at 9% with a durability value of 99.54%, density 1 g/cm3 and water content 5.39%.